2019
DOI: 10.1097/j.pain.0000000000001640
|View full text |Cite
|
Sign up to set email alerts
|

Altered microbiome composition in individuals with fibromyalgia

Abstract: Fibromyalgia (FM) is a prevalent syndrome, characterised by chronic widespread pain, fatigue, and impaired sleep, that is challenging to diagnose and difficult to treat. The microbiomes of 77 women with FM and that of 79 control participants were compared using 16S rRNA gene amplification and whole-genome sequencing. When comparing FM patients with unrelated controls using differential abundance analysis, significant differences were revealed in several bacterial taxa. Variance in the composition of the microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
177
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(191 citation statements)
references
References 89 publications
8
177
4
2
Order By: Relevance
“…1) shows the selection process and number of studies included and excluded at each step to arrive at the final eleven studies, conducted in 7 countries, included in this analysis. There was a high degree of heterogeneity across the studies, which were of variable quality ( (22)(23)(24)(25), and three reported other biomarkers (16,21,26). Four studies (16,(21)(22)(23) examined more than one type of biomarker and so are included in each of the appropriate sections below.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1) shows the selection process and number of studies included and excluded at each step to arrive at the final eleven studies, conducted in 7 countries, included in this analysis. There was a high degree of heterogeneity across the studies, which were of variable quality ( (22)(23)(24)(25), and three reported other biomarkers (16,21,26). Four studies (16,(21)(22)(23) examined more than one type of biomarker and so are included in each of the appropriate sections below.…”
Section: Resultsmentioning
confidence: 99%
“…The urinary microbial metabolism data reported in two of the studies included in this review were obtained from the same cohort (24,25). Two other studies evaluated serum markers for a range of metabolites, proteins and gene expression (22,23), and three compared patients with more than one type of control (23)(24)(25). These are summarised in Table 5.…”
Section: Metabolomics/metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lubrano et al (21) also found a significant association between fibromyalgia and the severity of IBS symptoms (p = 0.002). Emerging evidence suggests that the gut bacterial community may be altered in IBS (69), constipation (70), and in fibromyalgia (71). This is supported by pain reduction subsequent to antibiotic treatment (72) and following Marum's dietary intervention in patients with fibromyalgia (31).…”
Section: Discussionmentioning
confidence: 98%
“…Fibromyalgia therefore has clear correlations at the level of TMJ and oral health. In particular, as can be seen from the results, patients with TMD and FM show an increase in symptoms [41][42][43][44][45]. Fibromyalgia is diagnosed due to the exclusion of other pathologies and subsequent palpation of the tender points, although it is the patient's overall symptomatic picture that leads to diagnosis.…”
Section: Summary Of Evidencementioning
confidence: 98%